Chapter The use of initial h- in the writing-tablets from Roman Britain - Cotugno, Francesca (Lemmata Linguistica Latina, 2020)
These volumes assemble contributions presented at the XIX International Colloquium on Latin Linguistics in Munich (2017). They embrace essential topics of Latin linguistics with different theoretical and methodological approaches: The volumes contain chapters on Latin lexicography, etymology, morphology, phonology, Greek-Latin language contact, Latin syntax, semantics, and discourse-pragmatics.